The challenges of illegal trafficking in the Mediterranean Area - Militeo, Vicenzo; Spena, Alessandro (Legal Studies in International, European and Comparative Criminal Law, 2023)
Introduction 1 The illicit trades of people and goods in the Mediterranean and the transnational criminal organizations -- Section I – Jurisdictional issues -- 2 Territorialising the extraterritorial: the role of “suppression” conventions -- 3 Adjudicative Jurisdiction for crimes at sea: an international law perspective -- 4 Coercive powers and jurisdiction on the high seas to combat human smuggling -- Section II – Migrant smuggling -- 5 Anti-smuggling penal policies: a cross-national exploration -- 6 Facilitation of irregular immigration vs. organised smuggling of migrants: is this dichotomy relevant to the interpretation of Italian criminal law? -- 7 Challenging the hostile environment for search and rescue at sea: reflections from the Sea Watch litigation -- Section III – Human trafficking and labour market -- 8 The Problems of trafficking in human beings in Spain. Criminal regulations and Jurisprudential treatment -- 9 Organised crime, illicit manpower brokerage and recent Italian legislation -- 10 International and domestic perspectives to combat gangmaster systems -- Section IV – Traffickings of goods and human organs -- 11 Soft drugs and organized crime: a problematic relationship -- 12 Trafficking in cultural property. An evolving international legal framework -- 13 The criminal policy on trafficking in cultural goods14 Trafficking in human organs – a Portuguese perspective.